Preliminary Study of the Use of Sulphonated Polyether Ether Ketone (SPEEK) as Proton Exchange Membrane for Microbial Fuel Cell (MFC) - Permana, Dani; Putra, Herlian Eriska; Djaenudin, Djaenudin (International Journal of Renewable Energy Development, 2018)
Sulfonated polyether ether ketone (SPEEK) was utilized as a proton exchange membrane (PEM) in Microbial Fuel Cell (MFC). The SPEEK performance in producing electricity had been observed in MFC using wastewater and glucose as substrates. The MFC with catering and tofu wastewater produced maximum power density about 0.31 mW/m2 and 0.03 mW/m2, respectively, lower that of MFC with tapioca average power density of 39.4 W/m2 over 48 h. The power density boosted because of the presence of Saccharomyces cerevisiae as inoculum. The study using of S. cerevisiae and Acetobacter acetii, separately, were also conducted in with glucose as substrate. The MFC produced an average power densities were 7.3 and 6.4 mW/m2 for S. cerevisiae and A. acetii, respectively. The results of this study indicated that SPEEK membrane has the potential usage in MFCs and can substitute the commercial membrane, Nafion.Article History: Received: Juni 14th 2017; Received: Sept 25th 2017; Accepted: December 16th 2017; Available onlineHow to Cite This Article: Putra, H.E., Permana, D and Djaenudin, D. (2018) Preliminary Study of the Use of Sulfonated Polyether Ether Ketone (SPEEK) as Proton Exchange Membrane for Microbial Fuel Cell (MFC). International Journal of Renewable Energy Development, 7(1), 7-12.https://doi.org/10.14710/ijred.7.1.7-12